2012
DOI: 10.1111/acv.12005
|View full text |Cite
|
Sign up to set email alerts
|

Is Typhoid Mary a good role model?

Abstract: Read the Feature Paper: http://dx.doi.org/10.1111/j.1469-1795.2012.00564.x Other Commentaries on this paper: http://dx.doi.org/10.1111/acv.12008 Response from the authors: http://dx.doi.org/10.1111/acv.12011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although the parasite decreases survival of metamorph toads under laboratory conditions (Kelehear et al 2009), it has similar negative effects on some native frogs (Pizzatto and Shine 2011). The vulnerability of native anurans suggests that any attempt to increase parasite density (for toad-control) might 'spill over' and adversely affect native amphibians (Harris 2012;Hough-Goldstein 2012;Pizzatto and Shine 2012b). In wild toads, lungworms reduce the growth rates of their hosts, as well as the diversity of prey items consumed (HeisePavlov et al 2014;Kelehear et al 2011a) and affect the toad's cardiac response to exercise (Pizzatto and Shine 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the parasite decreases survival of metamorph toads under laboratory conditions (Kelehear et al 2009), it has similar negative effects on some native frogs (Pizzatto and Shine 2011). The vulnerability of native anurans suggests that any attempt to increase parasite density (for toad-control) might 'spill over' and adversely affect native amphibians (Harris 2012;Hough-Goldstein 2012;Pizzatto and Shine 2012b). In wild toads, lungworms reduce the growth rates of their hosts, as well as the diversity of prey items consumed (HeisePavlov et al 2014;Kelehear et al 2011a) and affect the toad's cardiac response to exercise (Pizzatto and Shine 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies revealed that R. pseudosphaerocephala is capable of successfully infecting native tree frogs, and is rapidly fatal to one iconic taxon, the magnificent tree frog, Litoria splendida (Pizzatto and Shine 2011). Although habitat differences between cane toads and the vulnerable frog may limit collateral impact (Pizzatto et al 2014), biocontrol using the toad lungworm may confer risks to native anurans (Harris 2012;Hough-Goldstein 2012). In addition, given that toad abundance is often high in populations that are rife with Rhabdias (Pizzatto et al 2013), it is unlikely that the lungworm, on it own, can reduce toad numbers (Pizzatto et al 2013;Pizzatto and Shine 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent paper (Pizzatto & Shine, ) suggested a new approach that may help to manage invasive cane toads ( Rhinella marina ) in Australia: the use of a native frog species as a ‘Typhoid Mary’ to spread a lungworm Rhabdias pseudosphaerocephala to toads. Both commentaries elicited by that paper (Harris, ; Hough‐Goldstein, ) suggest that we are too optimistic about the effectiveness of lungworm dissemination for toad control, and too dismissive of potential collateral impacts of our method on native species. Nonetheless, the commentaries are in broad agreement with us about the nature of costs and benefits involved.…”
mentioning
confidence: 99%